Comparing Greenhouse Gas Emissions from Municipal Solid Waste Management Scenarios: A case of Palembang, Indonesia - Tuti Alawiyah; Febrian Hadinata; Daniel Saputra; Ngudiantoro Ngudiantoro (Program Pascasarjana Universitas Sriwijaya, 2023)
The waste sector is one of the largest contributors to greenhouse gas (GHG) emissions in Indonesia. Landfilling (without methane recovery) and open burning of solid waste contribute significantly to GHG emissions. This study analyses the magnitude of GHG emissions from various municipal solid waste management (MSW) alternatives in Palembang city. The estimation of GHG emissions was conducted for five waste management scenarios, i.e. (a) BAU scenario (existing) where 850.12 tonnes of MSW is disposed in semi-aerobic landfill (not well managed), 37.73% in open incinerators, 1.17% in 3R facilities, and 61.1% others; (b) Scenario 1, in which the landfill is upgraded to a semi-aerobic (well managed); (c) Scenario 3, in which 70% of MSW is disposed in semi-aerobic (well managed) and 30% is disposed in 3R facilities; and (e) Scenario 4, in which all collected MSW is treated in incinerators. The methodology for estimating GHG emissions used IPCC 2006 (revised 2019). The Emission Quantification Tool from IGES is used to calculate GHG emissions from collection, transportation, composting, recycling/upcycling, and final disposal (landfill or incineration). The scenario is projected up to the year 2030, in accordance with the Indonesian NDC. The result of the analysis shows that the existing condition (BAU) has the highest GHGs emissions (730,767 tonnes CO2e). Scenario -4 has the lowest GHG emissions (117,954 tonnes CO2e). Therefore, 3R activities are the most important success factor for reducing GHG emissions in the MSW sector. Further financial analysis studies and multi-stakeholder engagement are needed for these scenarios to plan for sustainable MSW management.